2011
DOI: 10.1111/j.1651-2227.2011.02288.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up studies of very low birthweight children in Sweden

Abstract: The time has come to implement evident data from these Swedish follow-up studies into clinical practice and to perform regular and specific follow-up examinations during childhood for all VLBW and EPT children. These assessments, specially designed for high-risk infants, should consider the potential outcomes for neurological, visual, auditory function and cognitive function as well as behaviour and growth, from birth to school-start.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
1
8
0
1
Order By: Relevance
“…By international standards, the socioeconomic characteristics are satisfactory and high quality care is universally available in Sweden. Furthermore, alcohol or drug abuse during pregnancy is relatively rare (Gäddlin, 2011). These factors make it possible to investigate the impact of premature birth per se on cognitive development.…”
Section: Methodological Strengths and Challengesmentioning
confidence: 99%
“…By international standards, the socioeconomic characteristics are satisfactory and high quality care is universally available in Sweden. Furthermore, alcohol or drug abuse during pregnancy is relatively rare (Gäddlin, 2011). These factors make it possible to investigate the impact of premature birth per se on cognitive development.…”
Section: Methodological Strengths and Challengesmentioning
confidence: 99%
“…In Japan, it has increased from 4.1% of all live births in 1980 to 5.7% in 2010 (Japan Ministry of Health, Labour and Welfare, 2011). Medical advancements in neonatology have significantly increased the survival rate of preterm infants (Larroque et al, 2004; Fanaroff et al, 2007; Gaddlin, 2011; Kono et al, 2011). Recent reports have indicated an approximate survival rate of 90% in Japan for preterm infants with birth weights below 1500 g (Kusuda et al, 2006; Itabashi et al, 2009; Kono et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent long-term follow-up studies have suggested that preterm infants without apparent brain injuries are at risk for behavioral, educational, and emotional problems [2], [6] and are more likely to meet the criteria for developmental disorders such as attention-deficit hyperactivity disorder (ADHD) [7], pervasive developmental disorders [8], learning disabilities [9], and psychiatric disorders such as anxiety disorders and depression [10]. Although clear relationships have been demonstrated between preterm infants and developmental problems that occur later in childhood and adolescence, little is known about the early indications of these problems.…”
Section: Introductionmentioning
confidence: 99%